Mental Health as the Key to Learning Motivation among Psychology Students with Dual Roles - Natasya, Natasya; Srefani, Cornelia; Darma Sambo, Surya; Rizki Fadhila, Sherly; Sari, Nurvica; Mirza, Rina; Ayu, Lodiana (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
Mental health and learning motivation are two very important factors in higher education, as both directly impact academic achievement and student well-being. High learning motivation can help students stay more focused and committed to their studies, while good mental health supports their ability to manage stress and academic challenges. Although many studies discuss these two factors separately, few have examined the relationship between learning motivation and mental health, especially in students who work while studying. This study aims to identify the relationship between learning motivation and mental health among students at the Faculty of Psychology, Universitas Prima Indonesia, who are also working while attending classes. Using a quantitative approach with Pearson's correlation technique, this study involved 146 students as the sample. The results show a significant positive relationship between learning motivation and students' mental health, with a correlation value of 0.746 and a significance of p = 0.000, meaning that the higher a student's motivation to learn, the better their mental health. These findings highlight the importance of learning motivation in supporting students' psychological well-being. Educational institutions can develop programs that support the enhancement of both learning motivation and students' mental health, particularly for those who work while studying, to help them effectively cope with academic and personal challenges.Kesehatan mental dan motivasi belajar adalah dua faktor yang sangat penting dalam dunia pendidikan tinggi, karena keduanya berpengaruh langsung terhadap prestasi akademik dan kesejahteraan mahasiswa. Motivasi belajar yang tinggi dapat membantu mahasiswa untuk lebih fokus dan berkomitmen terhadap studi individu, sementara kesehatan mental yang baik mendukung kemampuan individu dalam mengelola stres dan tantangan akademik. Meskipun banyak penelitian yang membahas keduanya secara terpisah, belum banyak yang mengkaji hubungan antara motivasi belajar dan kesehatan mental, terutama pada mahasiswa yang bekerja sambil kuliah. Penelitian ini bertujuan untuk mengidentifikasi hubungan antara motivasi belajar dan kesehatan mental pada mahasiswa Fakultas Psikologi Universitas Prima Indonesia yang menjalani perkuliahan sambil bekerja. Menggunakan pendekatan kuantitatif dengan teknik korelasi Pearson, penelitian ini melibatkan 146 mahasiswa sebagai sampel. Hasil penelitian menunjukkan adanya hubungan positif yang signifikan antara motivasi belajar dan kesehatan mental mahasiswa, dengan nilai korelasi sebesar 0.746 dan signifikansi p = 0.000, yang berarti semakin tinggi motivasi belajar seorang mahasiswa, semakin baik pula kesehatan mental individu. Temuan ini menggarisbawahi pentingnya motivasi belajar dalam mendukung kesejahteraan psikologis mahasiswa. Lembaga pendidikan dapat mengembangkan program yang mendukung peningkatan motivasi belajar serta kesehatan mental mahasiswa, terutama bagi individu yang bekerja sambil kuliah, guna membantu individu mengatasi tantangan akademik dan kehidupan pribadi secara lebih efektif.